Two new species of the genus Emertonia Wilson, 1932 from Korean waters (Copepoda, Harpacticoida, Paramesochridae) - Back, Jinwook (Zookeys, 2017)
Abstract. Two new species of the genus Emertonia were found from the west coast of Korea. The first new species, E. koreana sp. n., is closely related to E. acutifurcata. However, the new species is clearly distinguished by the presence of two modified pinnate setae on the P5 baseoendopodal lobe. All body somites of the new species except for the last two urosomites have strongly developed hyaline frills forming quadrilateral lappets. The second new species, E. simplex sp. n., superficially resembles E. mielkei in the structure of antennary exopod (with five setae), and the shape of P5. However, this new species differs from its congener mainly by having a caudal ramus 3.5 times as long as width, and P1 enp-2 with two claw-like setae. In addition, a key to the worldwide species of Emertonia is provided.